The neuroinflammation marker translocator protein is not elevated in individuals with mild-to-moderate depression: A [11C]PBR28 PET study - Hannestad, Jonas; DellaGioia, Nicole; Gallezot, Jean-Dominique; Lim, Keunpoong; Nabulsi, Nabeel; Esterlis, Irina; Pittman, Brian; Lee, Jae-Yun; O’Connor, Kevin C.; Pelletier, Daniel; Carson, Richard E. (Brain, behavior, and immunity, 2013)
•Individuals with mild-to-moderate depression without systemic inflammation do not have neuroinflammation, as measured with PET imaging. Depression is associated with systemic inflammation. In animals, systemic inflammation can induce neuroinflammation and activation of microglia; however, postmortem studies have not convincingly shown that there is neuroinflammation in depression. The purpose of this study was to use positron emission tomography (PET) with [11C]PBR28, which binds to the neuroinflammation marker translocator protein 18kDa (TSPO), to compare the level of TSPO between individuals with depression and control subjects. Ten individuals who were in an acute episode of major depression and 10 control subjects matched for TSPO genotype and other characteristics had a PET scan with arterial input function to quantify levels of TSPO in brain regions of interest (ROIs). Total volume of distribution (VT) of [11C]PBR28 was used as a measure of total ligand binding. The primary outcome was the difference in VT between the two groups; this was assessed using a linear mixed model with group as a between-subject factor and region as a within-subject factor. There was no statistically significant difference in [11C]PBR28 binding (VT) between the two groups. In fact, 7 of 10 individuals with depression had lower [11C]PBR28 binding in all ROIs compared to their respective genotype-matched control subjects. Future studies are needed to determine whether individuals with mild-to-moderate depression have lower TSPO levels and to assess whether individuals with severe depression and/or with elevated levels of systemic inflammation might have higher TSPO levels than control subjects.